Latest trends for structural steel protection by using intumescent fire protective coatings: a review - Yasir, Muhammad; Ahmad, Faiz; Yusoff, Puteri Sri Melor Megat; Ullah, Sami; Jimenez, Maude (Surface engineering, 2020)
Intumescent coating (IC) is one of the famous protection systems for steel structures in the event of fire. Over the last few decades, ICs have been gaining much attention because they are applied on steel structure as fire protection. Upon exposure to flame, the coatings burn and swell, forming a heat shield called char. The formed char plays a critical role in protecting the steel substrate from the sudden rise in temperature which in return maintains the structural integrity of steel. In view of the importance of ICs, especially to the oil and gas sector, this paper reviews recent work on materials used for coatings and processing techniques for IC formation. The paper also gathers the latest information that focuses on ICs' main binders, flame retardant additives, and fillers. Finally, important issues in regard to durability and reliability of coatings in different environments are also highlighted.